Bautistas y presbiterianos en la política religiosa de Francisco J. Múgica y Sidronio Sánchez Pineda, 1920-1924 - Mendoza García, Leticia (El Colegio de México, A.C., 2018)
This article analyzes the way in which Baptist and Presbyterian missionaries operating in Michoacán between 1920 and 1924 developed strategies that spared them from the effects of Articles 3, 27 and 130 of the 1917 Constitution. It also studies the rapprochement between the Presbyterians and state and federal authorities, who were increasingly anticlerical. Protestant groups assumed a conveniently submissive and flexible attitude towards the authorities, securing the support of Governor Múgica, President Obregón and Interior Secretary Calles, who in turn used the missionaries to secure support for land reform and local anticlerical policies. Governors Mújica and Sánchez Pineda were themselves not interested in strengthening Protestantism at the expense of Catholicism, but nevertheless allowed Protestants to act because their obedience made them into non-hostile elements, as well as a convenient aid in the struggle against Catholicism. While there were Protestant congregations in most towns, this article centers on the churches in Morelia and Zitácuaro, as they were the center of activity for the state’s missionaries.